Βιβλιογραφικό σημείωμα: A. Agelarakis, Eastern Roman Mounted Archers and Extraordinary Medico-Surgical Interventions at Paliokastro in Thasos Island during the ProtoByzantine Period. The Historical and Medical History Records and the Archaeo-Anthropological Evidence, Summertown, Oxford 2020 - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2021)
Βιβλιογραφικό σημείωμα:A. Agelarakis, Eastern Roman Mounted Archers and Extraordinary Medico-Surgical Interventions at Paliokastro in Thasos Island during the ProtoByzantine Period. The Historical and Medical History Records and the Archaeo-Anthropological Evidence, Summertown, Oxford 2020